A randomized controlled trial of a structured exercise intervention after the completion of acute cancer treatment in adolescents and young adults. Issue 1 (16th October 2020) - Atkinson, Morgan; Murnane, Andrew; Goddard, Thomas; Pendergrast, Cathy; Rogers, Paul; Manudhane, Rebecca; Osborn, Michael
Abstract: Background: Cancer treatments are frequently associated with impaired physical fitness, quality of life (QOL), and fatigue, often persisting into survivorship.  Studies in older adults with cancer have demonstrated benefits from exercise; however, this has not been rigorously investigated in adolescents and young adults (AYA). The aim of this study was to determine whether a structured 10‐week exercise intervention was associated with improved cardiorespiratory fitness (VO2peak ), fatigue, and QOL in AYA who have recently completed cancer treatment. Method: Forty‐three AYA (median age 21 ± 6 years) were randomly assigned to an exercise group ( n  = 22) or a control group ( n  = 21). The exercise group received a structured 10‐week exercise program comprising progressive aerobic and resistance exercise; the control arm received routine care. VO2peak was measured at baseline, 10 weeks, and six months. Fatigue and QOL were assessed by the FACIT fatigue scale and the PEDS QL, respectively. Results: Mean VO2peak at baseline was 26.5 ± 7.2 mL.kg −1 .min −1, which is substantially lower than population norms. The exercise group demonstrated significant improvement in VO2peak at 10 weeks compared with controls (33.8 ± 8.1 vs 29.6 ± 7.6 mL.kg −1 .min −1, P  = 0.0002), but by six months, the difference was no longer significant (32.9 ± 7.0 vs 30.9 ± 11.0 mL.kg −1 .min −1, P  = 0.21). There were no significant differences in fatigue or total QOL scores between groups. Conclusion: Cancer treatment is associated with reduced VO2peak in AYA. Improvement in VO2peak was accelerated by a 10‐week exercise program; however, no significant benefit was observed in QOL or fatigue. The plateau in VO2peak at six months suggests that a maintenance exercise program may be beneficial.